ANALISIS FINANSIAL REHABILITASI AREAL EKS IUPHHK-HA PT KALANG MURNI DI PROVINSI KALIMANTAN TENGAH : Christopheros, Marthinus R. Lambung, Johanna M.R., dan Gimson Luhan - Admin JHT (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2017)
ABSTRACK Production forest management in Indonesia had been developed using a pattern of forest concessions (IUPHHK) since 1970s. In the development portion has ended a period of concession for 20 years. Forest areas that are not burdened the forest concessions or other rights, then the management is partly handed back to the goverment, and some management handed over by other appliances as Timber Utilization Permit (IPK). In connection with that carried a 0,3% timber cruising activities in the work areas of PT. ? Kalang Murni to obtain details about the condition of the standing stock. According on the analysis results, the standing stock of commercial trees in the group of diameter ? 20 cm contain average number of 25.5 stems/ha and average volume of 15.69 m3/ha, and the standing stock of other timber in the group of diameter ? 20 cm contain average number of 27.3 m3/ha, and average volume of 20.57 m3/ha. With the result that the total standing stock of the tress at the secondary forest of PT. Kalang Murni contain average number of 52.8 stems/ha and and average volume of 36,26 m3 / ha. According to the financial analysis, the Indonesia Strip Cutting and Planting (TJTI) system is suitable applied at the site when the interest rate in the position of 18%, whereas the Clear Cutting and Artificial Regeneration (THPB) system is not suitable at the same of interest rate. Keyword: Financial, forest concession, secondary forest, standing stock